(untitled) (Journal of Management & Business Studies, 2022)
The inclusion of the Sustainable Development Goals (SDG) in institutions is the challenge that organizations face worldwide. The importance of the SDGs for a company is reflected by the impacts that the company generates when it commits to them; in this way the company can identify the social, economic and environmental impacts. The application of the SDGs in companies brings with it a good corporate image, a good reputation and an improvement in the relationship with its stakeholders. The province of San Juan Argentine, has begun its path with sustainability and has committed to the SDGs, beginning to apply it in its State policies. This commitment is still incipient in the companies of the province in the present investigation has as objective to measure the commitment with the sustainability of the mining companies of the province of San Juan for the year 2022. The methodology chosen is qualitative, theory based on the use of software (Gibbs, 2007). The findings of the study are that the mining companies in the Province of San Juan are beginning to include the SDGs, their levels of sustainability communication being very low and this harms their social license to operate. Obviously this represents an opportunity for mining companies in the province.